Profitability Analysis of Cultivation of Banana Cultivars Sabri and Sagar in Some Areas Of Narsingdi District (Bangladesh Journal of Agricultural Research, 2022)
An attempt was made to investigate the input use pattern, profitability and factors affecting the banana cultivation. A total of 60 banana growing farmers taking each 30 Sabri and 30 Sagar growers were selected from Narsingdi district for collecting data using a pre-tested interview schedule during mid-September to mid-October, 2019. The study revealed that farmers used almost all types of inputs like human labour, organic and inorganic fertilizers, pesticides, and irrigation water in banana cultivation. The cultivations of both Sabri and Sagar variety were highly profitable at farm level since the net returns (Tk.4,29,280/ha and Tk.2,73,995/ha) and BCRs (2.66 and 2.05) were very high. The coefficients of production function revealed that banana sucker, land preparation and Muriate of Potash (MoP) fertilizer positively influenced the yield of Sabri variety banana, whereas only MoP influenced the yield of Sagar variety. The major problems of banana cultivation were lacking of skilled labour, attack of diseases, and high price of fertilizers.Bangladesh J. Agril. Res. 45(2): 175-183, June 2020